Triglyceride and Glucose Index and Sex Differences in Relation to Major Adverse Cardiovascular Events in Hypertensive Patients Without Diabetes - Yang, Kun; Liu, Wenxian (Frontiers in Endocrinology, 2021)
Introduction: Studies from decades suggested women had a lower risk of cardiovascular disease than men due to their characteristics, but hyperglycemia and hyperinsulinemia caused by IR (Insulin resistance) might reverse its gender-protective effect. We studied whether there were sex differences in the relationship between IR (evaluated by triglyceride and glucose index (TyG index)) and major adverse cardiovascular events (MACEs) in hypertensive patients without diabetes Methods: This was a post-hoc analysis of the Systolic Blood Pressure Intervention Trial (SPRINT). We explored the relationship between TyG index and MACEs by multivariate Cox proportional hazard regressions and two-piecewise linear regression models. The primary endpoint was MACEs, same as SPRINT, defined as a composite of myocardial infarction, stroke, heart failure, and/or death from cardiovascular causes. We used multiple adjustment models for all regressions. Results: 9323 patients from the SPRINT were included in our analysis. TyG index was significantly related to the risk of MACEs in every adjusted model. Each 1 unit increase in TyG index increased the risk of MACEs in total participants (HR, 1.40; 95% CI, 1.20-1.64; P<0.01) and men (HR, 1.42; 95% CI, 1.18-1.71; P=0.02). However, TyG index were not associated with MACEs among female hypertensive patients (HR, 1.33; 95% CI, 0.97-1.82; P=0.0776). There was no interaction between the sex and TyG index (P for interaction= 0.73). We also used the two-stage linear regression model, and we did not find any threshold effect. There was no significant interaction in other confounders. Conclusion: We found the Tyg index was associate with MACEs in the hypertensive patients, and there was no gender difference between Tyg index and MACEs.